NOTES ON THE GENUS MAPANIA (MAPANIOIDEA; CYPERACEAE) FROM TAMA ABU, SARAWAK - Shabdin, Z.; Meekiong, Kalu; Miraadila, M.I.; Ivy Geradlyn, N.; Aimi Syazana, Sedek; Syauqina, M.Y.; Yazid, K.; Shirley, C. (2019)
A list of Mapania species from Tama Abu PF of Heart of Borneo (HoB) area is presented in this paper. Tama Abu PF is considered fairly rich with Mapania species. Nine taxa were recorded of which one species is still undetermined.